TSC22D4 interacts with Akt1 to regulate glucose metabolism - Demir, Sevgican; Wolff, Gretchen; Wieder, Annika; Maida, Adriano; Bühler, Lea; Brune, Maik; Hautzinger, Oksana; Feuchtinger, Annette; Poth, Tanja; Szendrödi, Julia; Herzig, Stephan; Üstünel, Bilgen Ekim (Science advances, 2022)
Maladaptive insulin signaling is a key feature in the pathogenesis of severe metabolic disorders, including obesity and diabetes. Enhancing insulin sensitivity represents a major goal in the treatment of patients affected by diabetes. Here, we identify transforming growth factor-β1 stimulated clone 22 D4 (TSC22D4) as a novel interaction partner for protein kinase B/Akt1, a critical mediator of insulin/phosphatidylinositol 3-kinase signaling pathway. While energy deprivation and oxidative stress promote the TSC22D4-Akt1 interaction, refeeding mice or exposing cells to glucose and insulin impairs this interaction, which relies on an intrinsically disordered region (D2 domain) within TSC22D4. Functionally, the interaction with TSC22D4 reduces basal phosphorylation of Akt and its downstream targets during starvation, thereby promoting insulin sensitivity. Genetic, liver-specific reconstitution experiments in mice demonstrate that the interaction between TSC22D4 and Akt1 improves glucose handling and insulin sensitivity. Overall, our findings postulate a model whereby TSC22D4 acts as an environmental sensor and interacts with Akt1 to regulate insulin signaling and glucose metabolism.